Anti-Inflammatory Activity and Free Radical Scavenging Activity of Tridax Procumbens Leaves-Based Chitosan Gel - R. Nandita; M. Jeevitha; Kaarthikeyan Gurumoorthy; Rajeshkumar Shanmugham; Sudarsan Ravichandran; Kethiswar Raj (Journal of Pharmacy and Bioallied Sciences)
Introduction: Tridax procumbens (TP) has been used as an anticoagulant and wound healer. Known by other names as Tridax daisy or coatbuttons, TP belongs to flowering plant species of Asteraceae family. The current study is conducted to analyze the anti-inflammatory and antioxidant activity of TP leaves extract-based chitosan (TPC) gel. Materials and Methods: Anti-inflammatory activity of TPC gel was assessed by bovine serum albumin (BSA) denaturation assay and egg albumin (EA) denaturation assay. Free radical scavenging activity was evaluated by DPPH (2,2-diphenyl-1-picrylhydrazyl) assay and hydroxyl radical scavenging (H2O2) assay. Results: Both BSA and EA assay showed that the TPC gel (test gel) demonstrated maximum inhibition at 50 μL concentration and lowest inhibition at 10 μL similar to commercially available gel. The antioxidant activity assays revealed that both standard and the test gel exhibited high inhibitory percentage at all tested concentrations. Conclusion: The anti-inflammatory and antioxidant assay results demonstrate that the investigated compounds, notably TP leaves extract-based chitosan gel, have the potential to be effective agents in moderating oxidative stress and lowering inflammation.